Impact of SiC technology in a three-port active bridge converter for energy storage integrated solid state transformer applications - Wang, Zhenyi; Castellazzi, Alberto; Saeed, Sarah; Navarro-Rodríguez, Ángel; Garcia, Pablo (2016)
Silicon Carbide (SiC) MOSFET power module has become commercially available in the past few years, and it is attractive in solid state transformers (SSTs) applications to replace Silicon (Si)-based IGBTs. This paper is focused on the efficiency comparison between a SiC MOSFET-based three-port active bridge converter (TAB) and a Si IGBT-based approach. The efficiency of the overall system, being one of its ports connected to the energy storage element (Lithium-Ion battery), is tested and analyzed. By swapping the switching frequency of the device, a significant efficiency improvement can be observed by SiC power devices. Experimental results indicated that an efficiency increment of around 2% can be brought by SiC MOSFET. Moreover, the battery losses can be reduced by a maximum of 8% with the increased switching frequency.